2015
DOI: 10.1007/s00442-015-3285-7
|View full text |Cite
|
Sign up to set email alerts
|

Does extreme environmental severity promote plant facilitation? An experimental field test in a subtropical coastal dune

Abstract: The stress gradient hypothesis (SGH) postulates how the balance between plant competition and facilitation shifts along environmental gradients. Early formulations of the SGH predicted that facilitation should increase monotonically with stress. However, a recent theoretical refinement of the SGH postulates stronger facilitation under moderate stress, followed by a decreasing role of facilitation in the most severe environments. We conducted field experiments along the most severe part of a coastal dune gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…Such temporal variation in plant-plant interactions under extreme drought stress does not support the original SGH and, instead, is more consistent with the recent refined SGH. Both field studies in water-limited environments and meta-analyses at species and community levels have also demonstrated that the intensity and/or importance of positive effects diminish under extreme drought stress, or shift to neutral or even negative effects (Tielbörger and Kadmon 2000, Maestre and Cortina 2004, Soliveres et al 2013, Castanho et al 2015, Liancourt et al 2017, O' Brien et al 2017, but see Lopez et al 2016. Contrary to the SGH, the results of these studies are highly inconsistent, since many other factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such temporal variation in plant-plant interactions under extreme drought stress does not support the original SGH and, instead, is more consistent with the recent refined SGH. Both field studies in water-limited environments and meta-analyses at species and community levels have also demonstrated that the intensity and/or importance of positive effects diminish under extreme drought stress, or shift to neutral or even negative effects (Tielbörger and Kadmon 2000, Maestre and Cortina 2004, Soliveres et al 2013, Castanho et al 2015, Liancourt et al 2017, O' Brien et al 2017, but see Lopez et al 2016. Contrary to the SGH, the results of these studies are highly inconsistent, since many other factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by a variety of ecologists (Butterfield 2009, Armas et al 2011, He et al 2013, Michalet et al 2014, Soliveres et al 2015, Liancourt et al 2017, the apparently opposing views of the original and recent versions of the SGH may stem from inter-study differences in the nature of stress gradients (resource or non-resource stress), life-history of response species (stress tolerant or competitively inferior), scale of study focus (community or species level), component of stress factors (single or multiple stresses), or whether the observed gradient is complete. Even though a large number of studies from various ecosystems have explored the SGH, empirical tests of the hypothesis in extreme environments remains insufficient (but see Armas et al 2011, de Bello et al 2011, Castanho et al 2015, Lopez et al 2016, Liancourt et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the species that are becoming dominants in the sand‐mined site are not those for what we have knowledge about their facilitative effects (i.e., nurse species) and this has implications for the conservation and restoration of these coastal sandy plains. Plant facilitation can have a crucial role in restoration ecology (Brooker et al., ) by positively affecting the emergence and survival of plant species (Gómez‐Aparicio, ) or increasing diversity at intermediary‐to‐high environmental severity conditions (Castanho et al., ; Michalet et al., ). However, facilitation will be irrelevant if the plant species known to have such potential positive effect in undisturbed sites are absent from restoring sites.…”
Section: Discussionmentioning
confidence: 99%
“…Positive interactions are common in restinga communities and explain, for example, the association between understory trees and isolated adult trees (Castanho, Oliveira, & Prado, ). Nevertheless, such positive effects can become neutral or even negative under extreme environmental conditions (Castanho, Oliveira, & Prado, ), being strongly dependent on life form (e.g., herbs, shrubs, trees, and climbers). Scarano et al.…”
Section: Introductionmentioning
confidence: 99%